Order Statistics of Inverse Pareto Distribution - Ghulam Mustafa; Muhammad Ijaz; Farrukh Jamal (Computational Journal of Mathematical and Statistical Sciences)
In this paper we study the distribution of order statistics of the inverse Pareto distribution. We consider the single and product moment of order statistics from inverse Pareto distribution. Also, we establish some recurrence relation for single moments of order statistics. The exact analytical expressions of entropy, residual entropy and past residual entropy for order statistics of inverse Pareto distribution is derived.